Agent-based modelling of the early stages of actin polymerisation required to drive endocytosis in Saccharomyces cerevisiae - Lewis P. Hancock; Ellen G. Allwood; John S. Palmer; Kathryn R. Ayscough; Mike P. Williamson (Scientific Reports)
Abstract Endocytosis is critical. Its complexity means that many aspects remain poorly understood. We have developed an agent-based model covering key components of actin filament generation in endocytosis in Saccharomyces cerevisiae. The model incorporates realistic values for rates, affinities, concentrations, and mobilities, and reproduces essential features of endocytosis, from the arrival of WASp/Las17 and its inhibitor Sla1 at the membrane up to the burst of actin polymerisation. The model yields relative rates and affinities for interactions that cannot be measured experimentally, and places limitations on plausible scenarios. Specifically, it reveals three novel findings. First, Las17 must form multimeric complexes. Second, de novo F-actin nucleation occurs in two stages, involving the slow formation of linear trimers, followed by rapid polymerisation once an additional actin monomer is positioned at the side of the aligned monomers. Third, competition between SH3 domains and other factors, including actin, is critical to ensure on/off switching. This requires: (1) tandem domains binding to adjacent polyproline sites outcompeting single domains; (2) these tandem domains being weakened in overall affinity through a reduction in avidity by competition with single SH3 domains. We conclude with a pathway that proposes how controlled actin polymerisation occurs, and raises implications for further testing.